MicroRNA-138-5p Targets Pro-Apoptotic Factors and Favors Neural Cell Survival: Analysis in the Injured Spinal Cord - Rodrigo M. Maza; María Asunción Barreda-Manso; David Reigada; Ágata Silván; Teresa Muñoz-Galdeano; Altea Soto; Ángela del Águila; Manuel Nieto-Díaz (Biomedicines, 2022)
The central nervous system microRNA miR-138-5p has attracted much attention in cancer research because it inhibits pro-apoptotic genes including CASP3. We hypothesize that miR-138-5p downregulation after SCI leads to overexpression of pro-apoptotic genes, sensitizing neural cells to noxious stimuli. This study aimed to identify miR-138-5p targets among pro-apoptotic genes overexpressed following SCI and to confirm that miR-138-5p modulates cell death in neural cells. Gene expression and histological analyses revealed that the drop in miR-138-5p expression after SCI is due to the massive loss of neurons and oligodendrocytes and its downregulation in neurons. Computational analyses identified 176 potential targets of miR-138-5p becoming dysregulated after SCI, including apoptotic proteins CASP-3 and CASP-7, and BAK. Reporter, RT-qPCR, and immunoblot assays in neural cell cultures confirmed that miR-138-5p targets their 3′UTRs, reduces their expression and the enzymatic activity of CASP-3 and CASP-7, and protects cells from apoptotic stimuli. Subsequent RT-qPCR and histological analyses in a rat model of SCI revealed that miR-138-5p downregulation correlates with the overexpression of its pro-apoptotic targets. Our results suggest that the downregulation of miR-138-5p after SCI may have deleterious effects on neural cells, particularly on spinal neurons.